Just go to bed - Mayer, Mercer, 1943- (New York : Golden Books ; Racine, Wis. : Western Publishing, 1983)
A small animal uses his imagination to avoid going to bed, but finally has to admit that he is sleepy.
"A Golden look-look book."
1 3 4 5 7 8 9 11 13 15 17 21 23 26 27 31 36
Keywords: Sleep -- Fiction -- Juvenile literature; Imagination -- Fiction -- Juvenile literature